GROUNDWATER VULNERABILITY OF PANDAK AND BAMBANGLIPURO, YOGYAKARTA SPECIAL PROVINCE, INDONESIA - Leakhena Snguon; Doni Prakasa Eka Putra; Heru Hendrayana (Journal of Applied Geology, 2015)
The study of intrinsic vulnerability of groundwater was generated in order to delineate groundwater protection zone in Pandak and Bambanglipuro, Indonesia, whose mainly water supply is from groundwater. Two methods of vulnerability mapping are chosen for the evaluation; DRASTIC method and Hoelting method. The resulted maps conducted from these method are validated using the actual contaminant concentration through the impact of on-site sanitation, for instance nitrate as it is proved to be very stable contaminants in groundwater. Considered in different hydrogeological setting, these two methods have produced various results at the certain site. However, its reliability has been drawn upon the nitrate concentration at the study areas. Keywords: Intrinsic groundwater, vulnerability, DRASTIC, Hoelting methods, nitrate contamination